2008
DOI: 10.1007/s00220-008-0690-3
|View full text |Cite
|
Sign up to set email alerts
|

Sharp Bounds on the Critical Stability Radius for Relativistic Charged Spheres

Abstract: In a recent paper by Giuliani and Rothman [16], the problem of finding a lower bound on the radius R of a charged sphere with mass M and charge Q < M is addressed. Such a bound is referred to as the critical stability radius. Equivalently, it can be formulated as the problem of finding an upper bound on M for given radius and charge. This problem has resulted in a number of papers in recent years but neither a transparent nor a general inequality similar to the case without charge, i.e., M ≤ 4R/9, has been fou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
212
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(222 citation statements)
references
References 26 publications
9
212
1
Order By: Relevance
“…By relaxing these assumptions and considering any static solution of the spherically symmetric Einstein equations for which the energy density ρ ≥ 0 and the radial and tangential pressures, p ≥ 0 and p T , satisfy the condition p + 2 p T ≤ ρc 2 , > 0, one can obtain the relation sup r >0 [2G M(r )/c 2 r ] ≤ [(1 + 2 ) 2 − 1]/(1 + 2 ) 2 [5]. These bounds were generalized to the case of charged compact general relativistic objects in [6]. Bounds on M/R for static objects with a positive cosmological constant > 0 were obtained in [7], where it was shown that the relation G M/c 2 R ≤ 2/9 − R 2 /3 + (2/9) √ 1 + 3 R 2 holds if the energy conditions listed above are satisfied.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…By relaxing these assumptions and considering any static solution of the spherically symmetric Einstein equations for which the energy density ρ ≥ 0 and the radial and tangential pressures, p ≥ 0 and p T , satisfy the condition p + 2 p T ≤ ρc 2 , > 0, one can obtain the relation sup r >0 [2G M(r )/c 2 r ] ≤ [(1 + 2 ) 2 − 1]/(1 + 2 ) 2 [5]. These bounds were generalized to the case of charged compact general relativistic objects in [6]. Bounds on M/R for static objects with a positive cosmological constant > 0 were obtained in [7], where it was shown that the relation G M/c 2 R ≤ 2/9 − R 2 /3 + (2/9) √ 1 + 3 R 2 holds if the energy conditions listed above are satisfied.…”
Section: Introductionmentioning
confidence: 92%
“…The physical implications of the existence of a minimum mass (in D = 4) were investigated in [15]. An especially important result is that the ratio l 4 Pl / , where l Pl is the reduced Planck length and is the four-dimensional cosmological constant, is numerically of the same order of magnitude as r 6 e , where r e ≈ 2.818 × 10 −13 cm denotes the classical electron radius. This suggests the identification of in terms of fundamental physical constants as …”
Section: Introductionmentioning
confidence: 99%
“…whereas the upper bound of the mass-radius of a charged sphere was generalized by Andréasson [50] as follows:…”
Section: Generalized Tov Equation For Solution Imentioning
confidence: 99%
“…The upper bound of the mass of charged sphere was generalized by Andréasson [191] and one proved that…”
Section: Elementary Criteria For Physical Acceptabilitymentioning
confidence: 99%